Cytoprotective activity of carrot and tomato callus extracts and the ex‐ pression of cytokines in UV‐B irradiated fibroblast cells - Rumiyati Rumiyati; Sismindari Sismindari; Endang Semiarti; Sitarina Widyarani; Dewi Tika Sari; Brilliant Kharisma Apritadila; Anami Riastri (Universitas Gadjah Mada, 2019)
Studies have suggested that both carrot (Daucus carota L.) and tomato (Solanum lycopersicum L.) callus extracts contain antoxidant compounds that might have the potental to protect cells from free radicals such as H2O2 that contribute to cell damage. The other sources of free radical exposure in human cells, such as UV‐B, should also be examined. UV‐B exposure can trigger increased expression of inﬂammatory cytokines such as cyclooxygenase‐2 (COX‐2) and tumor necrosis factor‐α (TNF‐α) and the antinﬂammatory cytokine interleukin‐10 (IL‐10), which causes photoaging. This study was conducted to investigate the cytoprotectve actvity of carrot and tomato callus aqueous extracts by observing cell viability using the MTT assay. Immunocytochemistry methods were used to examine the eﬀects of carrot and tomato callus aqueous extracts on the expression of COX‐2, TNF‐α, and IL‐10 in human dermal fibroblast adult (HDFa) cells exposed to UV‐B light. Carrot and tomato callus aqueous extracts were obtained by the maceration method using aqua bidistilled solvent. Results showed that both carrot and tomato callus aqueous extracts at 0.5 mg/mL exhibited the highest cytoprotective eﬀect in HDFa cells compared to that at other concentratons. Both carrot and tomato callus aqueous extracts could also decrease the expression of COX‐2 and TNF‐α, whereas carrot callus aqueous extract increased the expression of the anti‐inﬂammatory cytokine IL‐10 in HDFa cells.